Agile Development Of Restaurant Reservation Information System: A Case Study On Enhancing Efficiency And Cus-tomer Experience - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
This research focuses on the issues encountered in the restaurant industry, specifically the need for more efficiency and optimal customer experience in restaurant reservation systems. The study employs the Agile Development methodology, which consists of three main stages: System Requirements Analysis, Application Design and Implementation, and Testing and Evaluation. Key features such as reservation management, customer notifications, payment system integration, and performance reporting are carefully implemented. Subsequently, during the Testing and Evaluation stage, functional testing, performance testing, and overall system testing are conducted to ensure that the system operates as expected, is responsive to high loads, and features integration runs smoothly. User evaluation involving stakeholders and end-users is conducted to gather final feedback before the official launch. The outcome of this research is developing an efficient, responsive, integrated restaurant reservation system that provides a more satisfying customer experience. The research enhances restaurant operational efficiency, responsiveness to customer needs, and overall customer experience through a comprehensive, integrated reservation system.